THROMBOEMBOLIC DISEASES ON THE BACKGROUND OF COVID -19 - Nodirbek Ilkhomjon ogli Yakubov (Web of Journals Publishing, 2023)
Currently, it can be noted that COVID-19 is, without exaggeration, the most serious challenge to the international system of practical healthcare in its recent history. Extremely high morbidity and mortality rates dictate the need for a more detailed study of the pathogenetic aspects of the developing infectious disaster. In addition to respiratory distress syndrome, systemic inflammatory reaction syndrome, COVID-19 is characterized by polyvalent disorders of the mechanisms of systemic hemostasis, which is reflected in the increase in the number of venous thromboembolic complications in the overall structure of morbidity and mortality. The above literature review summarizes information on COVID-19-associated coagulopathy and its effect on changes in the clinical and epidemiological characteristics of venous thromboembolic complications.
Keywords: COVID-19; SARS-CoV-2; venous thromboembolic complications; Co-associated coagulopathy.